2021
DOI: 10.1007/s10686-021-09809-6
|View full text |Cite
|
Sign up to set email alerts
|

Time domain astronomy with the THESEUS satellite

Abstract: THESEUS is a medium size space mission of the European Space Agency, currently under evaluation for a possible launch in 2032. Its main objectives are to investigate the early Universe through the observation of gamma-ray bursts and to study the gravitational waves electromagnetic counterparts and neutrino events. On the other hand, its instruments, which include a wide field of view X-ray (0.3-5 keV) telescope based on lobster-eye focussing optics and a gamma-ray spectrometer with imaging capabilities in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 392 publications
(463 reference statements)
0
6
0
Order By: Relevance
“…However, the extent and nature of the X-ray flows are not fully justified in accordance with these new models. It has been suggested that the accretion flows in nonmagnetic white dwarf binaries are well explained in the context of radiatively inefficient advective hot flows in the X-ray regime (Balman & Revnivtsev 2012;Balman 2020;Mereghetti et al 2021). This work is an extrapolation and development of our previous works on the two NLs regarding advection-dominated accretion flows in the X-rays (Balman et al 2014;Godon et al 2017).…”
Section: Introductionmentioning
confidence: 58%
“…However, the extent and nature of the X-ray flows are not fully justified in accordance with these new models. It has been suggested that the accretion flows in nonmagnetic white dwarf binaries are well explained in the context of radiatively inefficient advective hot flows in the X-ray regime (Balman & Revnivtsev 2012;Balman 2020;Mereghetti et al 2021). This work is an extrapolation and development of our previous works on the two NLs regarding advection-dominated accretion flows in the X-rays (Balman et al 2014;Godon et al 2017).…”
Section: Introductionmentioning
confidence: 58%
“…From ELT to ATHENA, CTA to Einstein Telescope, the Vera Rubin Observatory to the Roman Space Telescope, the science returns from combining observations with multiple facilities is a classic case of "the whole being much greater than the sum of the parts" [26]. A broad range of other science programmes will be enabled by THESEUS, including using observations of GRB emission as laboratories of ultra-relativistic matter and, e.g., for testing Lorentz invariance [5], as well as gathering statistics on large populations of other high-energy sources and transients [27]. Thus, THESEUS data will be of interest to a very wide user community, also through its open guest-observer programme.…”
Section: The Theseus Mission Conceptmentioning
confidence: 99%
“…At the same time, the goals for multi-messenger astrophysics and time domain astronomy require:(i) a substantial advance in the detection and localization, over a large (>2 sr) FoV of short GRBs as electromagnetic counterparts of GW signals coming from BNS, and possibly NS-BH mergers; (ii) monitoring the high-energy sky with an unprecedented combination of sensitivity, location accuracy and field of view in the soft X-rays; iii) imaging up to the hard X-rays and spectroscopy/timing of the soft gamma-rays [27,29,30].…”
Section: Scientific Goals and Requirementsmentioning
confidence: 99%
“…The Transient High-Energy Sky and Early Universe Surveyor (THESEUS) mission concept [1][2][3] aims at fully exploiting Gamma-Ray Bursts (GRB) for early Universe and multi-messenger astrophysics, as well as providing a substantial advance in time-domain astronomy through detection, accurate location, multi-wavelength (0.3 keV -10 MeV plus near IR) characterization, and redshift measurement, of many classes of high-energy transients [4][5][6][7][8][9] . Developed by a large international collaboration, in 2018 THESEUS was selected by ESA for a three years Phase 0/A study as one of the three candidates for the M5 medium-class space mission opportunity for a launch in ~2032 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This breakthrough performance can be achieved by overcoming the current limitations through an extension of the GRB monitoring passband to the soft X-rays with an increase of at least one order of magnitude in sensitivity with respect to previously flown wide-field X-ray monitors, as well as a substantial improvement of the efficiency of counterpart detection, spectroscopy and redshift measurement through prompt on-board NIR follow-up observations. At the same time, the objectives on multi-messenger astrophysics [5][6] and, more generally, time domain astronomy [7][8][9] and synergies with future very large facilities [10][11] , require: a) a substantial advancement in the detection and localization, over a large (> 2 sr) Field-of-View (FoV) of short GRBs as electromagnetic counterparts of GW signals coming from NS-NS, and possibly NS-BH) mergers; b) monitoring the high-energy sky with an unprecedented combination of sensitivity, location accuracy and field of view in the soft X-rays; c) imaging up to the hard X-rays and spectroscopy / timing to the soft gamma-rays.…”
Section: Introductionmentioning
confidence: 99%